Past Lives of Knives: On Borges, Translation, and Sticking Old Texts - Fraser, Ryan (TTR : traduction, terminologie, rédaction, 2004)
AbstractAs a rule, translation “nurtures” a text, extends its genealogy across cultural and historical divides. The strange account of this article is perhaps the exception that proves the rule. We’ll see a seventy-year old Jorge Luis Borges put heads together with a young Harvard man by the name of Norman Thomas di Giovanni and “re-write the slate clean,” translate old texts for the purpose of “sticking it” to them, suppressing them, even consigning them to oblivion. The collaboration was a bit of inspired naughtiness that we’ll call “translational infamy.” It had enduring consequences, for the good and bad, on the characters populating Borges’s writings and his private life. This equation of translation and oblivion, we’ll see it play out in Borges’s older fictions, specifically Pierre Menard; in the editorial logistics of his collaboration with Di Giovanni; in the creation—and simultaneous translation—of new fictions (Brodie’s Report); and, perhaps most interestingly, in the details of his own biography.